Peculiarities of Informal Music Education in an Inclusive Classroom: Analysis of Teachers’ Experiences - Šauklė, Ieva (Jaunųjų mokslininkų darbai, 2024)
Although more and more attention is paid to the development of inclusive education in Lithuanian education, but taking into account the fact that the success of any education depends on the ability of the pedagogue to work qualitatively in various conditions, inclusive education is still full of challenges. The article reviews the approach of researchers to non-formal music education when there are SEN children in the classroom, and also, through the empirical study, the challenges faced by pedagogues when teaching music students with special needs are revealed. The research revealed that the educational context of inclusion of non-formal music education is necessary, but full of challenges: lack of suitable conditions for working with children with SEN (addapted learning environment, variety of musical instruments, need for a teacher’s assistant), limited preparation of music educators for work in an inclusive classroom, insufficient knowledge of existing music and art school teachers about the development and learning characteristics of children with SEN.